Evaluasi Keefektifan Metode Moving Average dan Exponential Smoothing sebagai Pendekatan Statistik dalam Memprediksi Nilai Tukar Rupiah terhadap Dolar AS - Simanjuntak, Loranty Folia; Hawani, Saniah Lidiya; Nazura, Ananda; Sipahutar, Paskah Gloria S. (Program Studi Akuntansi PSDKU Universitas Pattimura, 2025)
Exchange rate of the Indonesian Rupiah against the US Dollar is a crucial economic indicator that significantly impacts Indonesia's macroeconomic stability. Exchange rate fluctuations can affect trade, investment, inflation, and monetary policy. Therefore, an accurate forecasting method is essential to support economic decision-making. This article aims to evaluate the effectiveness of Moving Average and Exponential Smoothing methods in predicting the Rupiah exchange rate against the US Dollar. Using a qualitative approach based on literature review, this study compares findings from various previous studies on these two methods. The analysis results indicate that Exponential Smoothing is more effective in highly volatile market conditions due to its adaptability to trend changes, while Moving Average performs better in stable market conditions. These findings provide insights for academics, financial analysts, and policymakers in selecting appropriate forecasting methods to support economic stability.